Mechanisms of nucleophilic substitutions of acetals - Bull, S; Correia, L; Davies, S (1998)
The nucleophilic substitution of (+)-(R)-benzaldehyde methyl isopropyl acetal (αR)-1 (93% ee) and (+)-(R)-o-anisaldehyde methyl isopropyl acetal (αR)-2 (homochiral) with Me2CuLi-BF3·OEt2 occurs completely chemoselectively to afford (+)-(αR)-α-methyl(benzyl) isopropyl ether (+)-(αR)-3 (40% ee) and (+)-(αR)-α-methyl(o-methoxybenzyl) isopropyl ether (+)-(αR)-4 (34% ee) respectively, demonstrating that the mechanism of the former reaction involves a free oxonium ion to the extent of 56% and the latter to the extent of 66%.